Control System for the Synthesis of Thin Films by Pulsed Laser Deposition - Conde Garrido, Juan Manuel (2020)
The pulsed laser ablation process is a widely used technique for thin films deposition. In this method, a pulsed laser beam focuses onto a target ablating the impact site, called spot. Since preparing the target is a highly time consuming and expensive task, the spot is generally scanned across the target?s surface. A typical pulsed laser deposition configuration has a moving mirror that scans the laser beam across a rotating target. We propose ablating the target with a spiral pattern to ensure a uniform ablation and maximizing the target?s efficiency. This requires moving the mirror and target in sync with variable speeds. To this end, we designed and built robust electromechanical actuators driven by stepper motors, which are electronically controlled by an Arduino-based system. The core of the firmware is a precalculated lookup table with the time intervals between the motors? steps. Thus, motor control following computationally expensive positioning functions -as the spiral pattern- are not a problem. Users may operate the control system through a user-friendly interface. The modular firmware architecture facilitates future extensions as, for example, adding other motor positioning functions to enable different ablation patterns for research purposes. This development aims to be a valuable tool for the synthesis of thin films by pulsed laser deposition.